The performance of psoriatic arthritis classification criteria in Turkish patients with psoriatic arthritis - Nas, Kemal; Karkucak, Murat; Durmus, Bekir; Ulu, Mehmet Ali; Karatay, Saliha; Capkin, Erhan; Ozgocmen, Salih (Wiley, 2017)
ObjectivesTo investigate performance of some of the published psoriatic arthritis (PsA) classification criteria as well as Assessment of Spondyloarthritis International Society (ASAS) criteria for peripheral spondyloarthritis (SpA) in Turkish patients with PsA (in early and late disease subgroups). MethodsPatients were recruited using case report forms and physical examination methods proposed by the Anatolian Group for the Assessment in Rheumatic Diseases (ANGARD). The Moll and Wright (MW), modified Fournie (MF), modified McGonagle (mMG), Vasey and Espinoza (VE), classification of PsA (CASPAR) criteria and ASAS criteria were assessed in patients with PsA who were diagnosed based on expert opinion. ResultsOne hundred and twenty-eight patients with PsA (58 male, 70 female, mean age 41.8years) were included. Thirty patients were in the early PsA and 98 patients were in the late PsA groups. Diagnostic delay was 2.6years. In the 15.6% of patients arthritis developed before the skin findings. The proportion of patients fulfilling the MW, MF, mMG, VE, CASPAR and ASAS criteria were at a ratio of 90.6%, 82.8%, 62.5%, 84.4%, 96.1% and 76.5%, respectively. In early PsA (< 12months disease duration) the proportions were 93.4%, 83.3%, 76.7%, 76.7%, 96.7% and 66.6%, respectively. On the other hand, in late PsA the proportions were 89.8%, 82.6%, 57.1%, 86.7%, 95.9%, 79.5%, respectively. ConclusionsEven though the sensitivity of PsA classification criteria in Turkish patients changes, the CASPAR criteria seems to be more prominent among all criteria for both early and late cases with its high sensitivity.
Keywords: classification criteria; early arthritis; psoriatic arthritis; spondyloarthritis